Prevalence of malnutrition and hyperglycemia in critically ill patients (Research, Society and Development, 2020)
The purpose of the study is to to perform a bibliographic search on the prevalence of malnutrition and hyperglycemia in critically ill patients. This is an integrative literature review. To search for and select the studies, the following databases were used: Scielo, Science Direct and Pubmed, allowing the selection of 9 articles, which were published between the years 2015 and 2019. It was verified that there is a large number of studies that clearly demonstrate the high prevalence of malnutrition and hyperglycemia in critically ill patients. These factors alone or in combination can generate numerous complications as well as organ failure, interfering with the improvement of the patient's clinical picture, and in some situations lead to death. It is necessary to carry out more studies, for the production of scientific information, and for society in general, so that anyone who is scientific or not can have access to them.